2008
DOI: 10.1111/j.1365-2133.2008.08799.x
|View full text |Cite
|
Sign up to set email alerts
|

How prominent are patient-reported outcomes in clinical trials of dermatological treatments?

Abstract: Asking study participants for their views of treatment efficacy seems like a good idea in dermatological clinical trials, yet only about a quarter of the trials examined in this review did so. Even when such information was recorded, it was often poorly and incompletely reported and given low prominence within the trial report. Our study findings call for a more comprehensive uptake for including participant efficacy outcomes alongside other assessor outcomes in clinical trials and, when included, to report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
13
1
Order By: Relevance
“…Despite this, in the 54 clinical trials analyzed in this review, only about one fourth included a patient-reported measure among the primary outcomes. These figures are quite similar to those of Townshend et al [10], who, in 2003, analyzed 125 dermatologic trials and found that only 32 of them (25.6 %) mentioned participant efficacy outcomes. Another study observed that, even when information on quality of life was available [11], methods and results were not adequately reported.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite this, in the 54 clinical trials analyzed in this review, only about one fourth included a patient-reported measure among the primary outcomes. These figures are quite similar to those of Townshend et al [10], who, in 2003, analyzed 125 dermatologic trials and found that only 32 of them (25.6 %) mentioned participant efficacy outcomes. Another study observed that, even when information on quality of life was available [11], methods and results were not adequately reported.…”
Section: Discussionsupporting
confidence: 87%
“…Comparability of PASI is most likely a myth, not only because of a lack of standardized comparative studies across institutions and countries but because of the vast diversity of times at which it is assessed as an outcome. In this review, even when only considering the primary outcomes, the change in PASI score was assessed in the different studies at weeks 4,6,8,10,12,14,16,20,25,52, and 160. In addition, one study used it at 35 sessions of phototherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, patient-centred outcomes have rarely been included in vitiligo trials, despite previous recommendations for inclusion in studies on vitiligo 1,4 and other dermatological conditions. 9 Therefore, it is important to create consensus among researchers to ensure that the outcomes used in the trials for vitiligo treatment are reliable, clinically relevant and important to both clinicians and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple end points may be needed to fully describe a multifaceted disease, such as acne. In other cases, multiple end points may arise from the need to get both a clinician's and a patient's assessment of efficacy (4). For example, in more cosmetic indications such as hair growth or glabellar lines, both the clinician's and subject's assessments may be important end points.…”
Section: Reported Efficacy and Safety Findingsmentioning
confidence: 99%